THE INFORMATION AGE IN COMMUNICATIONS AND ITS IMPACT ON CONSUMER BEHAVIOR IN THE TOURISM BUSINESS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In recent years, there has been an increased development of information technologies, which have a significant impact on the economic and social sphere worldwide and, in particular, on communications between consumers and companies. Dynamic changes in the global aspect of the economy and changes in consumer tastes and preferences are only part of the factors for the creation and integration of new modern technologies. It is the application of various technologies that is of key importance for communications with consumers in the tourism business.; Attesting to the relationship between customer satisfaction and the success of a company's experience generation strategy is complex. Consumers may be very satisfied but completely unmotivated to make additional trips or recommend the company to others. It is precisely in this process and the resolution of various challenges that information technology is essential.